Understanding the Family Business - Alderson, Keanon (Business Expert Press, 2011)
Ebook from IG Library ; Family business is the most prevalent form of organization in the world. It has been estimated that as many as 90% of businesses are either family owned or family controlled. A third of the Fortune 500 firms, as well as a third of the S & P 500, are family owned or controlled. In universities today, most courses focus on large, public corporations rather than on the long-term ownership issues of the more prevalent family business. This book will explore the main differences between family firms and non-family firms. The audience is students, business owners, professional service providers, and suppliers, for whom the book will provide an appreciation and understanding of the family business. This book will be ideal as a text for a general course on family business course or as a supplemental text for a course in small business, entrepreneurship or business management. It is also ideal for a family business owner or member who seeks to better manage the unique problems and issues inherent in a family firm.